Guide to collections relating to Oman (St Antony’s College, 2013)
Keywords: Inventaire – Oxford

Libyan Berber Heritage: Jefara, Adrar Nafusa and Hamada al Hamra Cultural Landscapes. A possible new Tentative Candidate for UNESCO List - Bencini, Claudio (Fondazione Onlus, 2013)
Libyan Berber Heritage: Jefara, Adrar Nafusa and Hamada al Hamra Cultural Landscapes. A possible new Tentative Candidate for UNESCO List
Keywords: Archéologie – Djebel Nefousa